Pengaruh Pengelolaan Kegiatan Main terhadap Interaksi Sosial Anak Usia 5-6 Tahun Di PAUD Cinta Bangsa - Narimah, Samaniati; Rachmayani, Ika; Jaelani, Abdul Kadir (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
The objective of this study is to ascertain the impact of managing play activities on the social interaction skills of children aged 5-6 years at PAUD Cinta Bangsa, East Pemenang Village, Pemenang District, North Lombok Regency. The research method employed is a Quantitative Quasi-Experimental Design, specifically a "pre-test and post-test with non-equivalent control group design." The population comprised 48 children aged 5-6 years at PAUD Cinta Bangsa. Nonprobability sampling technique with census sampling was employed, encompassing the total population of 48 children. Data collection techniques involved the administration of tests and non-participant observation. Data analysis techniques employed descriptive statistics, prerequisite tests of normality and homogeneity, independent paired sample t-test, independent t-test n-gain score. The results of the hypothesis testing, with a significance level of 5% (0.05), yielded a two-sided test value/two-tailed test value < 0.001 < 0.05. This finding indicates that H0 is rejected and Ha is accepted, thereby concluding that there is a significant influence between the management of play activities and children's social interaction.